Patterns of rDNA and telomeric sequences diversification: contribution to repetitive DNA organization in Phyllostomidae bats - Calixto, Merilane da Silva; Andrade, Izaquiel Santos de; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Santos, Neide; Martins, Cesar [UNESP]; Loreto, Vilma; Souza, Maria Jose de (Springer, 2014)
Chromosomal organization and the evolution of genome architecture can be investigated by physical mapping of the genes for 45S and 5S ribosomal DNAs (rDNAs) and by the analysis of telomeric sequences. We studied 12 species of bats belonging to four subfamilies of the family Phyllostomidae in order to correlate patterns of distribution of heterochromatin and the multigene families for rDNA. The number of clusters for 45S gene ranged from one to three pairs, with exclusively location in autosomes, except for Carollia perspicillata that had in X chromosome. The 5S gene all the species studied had only one site located on an autosomal pair. In no species the 45S and 5S genes collocated. The fluorescence in situ hybridization (FISH) probe for telomeric sequences revealed fluorescence on all telomeres in all species, except in Carollia perspicillata. Non-telomeric sites in the pericentromeric region of the chromosomes were observed in most species, ranged from one to 12 pairs. Most interstitial telomeric sequences were coincident with heterochromatic regions. The results obtained in the present work indicate that different evolutionary mechanisms are acting in Phyllostomidae genome architecture, as well as the occurrence of Robertsonian fusion during the chromosomal evolution of bats without a loss of telomeric sequences. These data contribute to understanding the organization of multigene families and telomeric sequences on bat genome as well as the chromosomal evolutionary history of Phyllostomidae bats.
Keywords: Chromosomal evolution; Fluorescence in situ hybridization; Multigene family; 5S; Phyllostomidae; Telomeric sequences